Management of Rice Sheath Blight Disease Using Commercially Available Fungicides in Kuttanad (Journal of Plant Disease Sciences, 2019)
Field experiments were conducted at Rice Research Station, Moncompu, Alappuzha, Kerala for five consecutive seasons of Rabi 2012-13, Kharif, 2013, Rabi, 2013-14, Kharif, 2014 and Rabi, 2014-15 with the objective of evaluation of efficiency of newer and commercially available fungicides against sheath of blight rice. Out of seven fungicides tested, Tebuconazole (Folicur 250 EC) @ 1.5 ml/l was found most effective followed by Pencycuron (Monceren 250 SC) and Tebuconazole 50% + Trifloxystrobin 25% (Nativo 75 WG).
Keywords: Sheath blight; Rice; Fungicide; Management